Molding of a passive sound-proof ear piece - Wong, Louis Fook Seng (2016)
Traditional earplugs block noise by sealing off the ear canal when inserted. Although this reduces the overall quantity of noise, it also causes its quality to deteriorate as well. This is due to uneven attenuation across the entire frequency range where certain frequencies are attenuated more than others. Wearers of traditional earplugs also experience the occlusion effect as a result of bone-conducted vibrations and fatigue due to pressure build-up. Hence, there exists a need to develop high fidelity hearing protection equipment that solves these problems. The objective of this project is to design a passive sound-proof earpiece, in which its form improves upon the abovementioned functional attributes. This design concept is then used to create a physical mold, from which its design is tested against parameter-performance variables. A low pass filter attenuates high frequencies while letting low frequencies pass through, and vice versa for a high pass filter Building upon this foundation, a acrylic earpiece which encapsulates these two acoustic filters was created. The earpiece was then tested against traditional earplugs in terms of attenuation quantity and quality, and also against variations of itself in order to properly identify the each component’s attenuation properties. The earpiece provided an overall attenuation of 16.5 dB which was not as good as the foam and flanged earplugs, but excelled in providing relatively even attenuation across the range of frequencies. This translates to having a better quality of sound. While this project provided telling results, it was not without its limitations. More precise numerical techniques and instruments are required to truly ascertain the accuracy of the experimental results. Nonetheless, the outcome of this project can prove useful to hearing protection manufacturers and the general public alike.